PERIPARTUM UROGENITAL DISORDERS IN MARES - Fernandes, Claudia Barbosa; Guimarães, Carina Fátima; Oliveira, Bruna Marcele; Oliveira, Guilherme Cain; Oliveira, Camila Gonçalves; Meirelles, Marcela Gonçalves; Celeghini, Eneiva Carla (Veterinária e Zootecnia, 2022)
Disease processes in peripartum period can adversely affect a mare´s future fertility or, worse, may be life threatening to her or her foal. An additional unique set of differential diagnosis must be considered in the mare at this time, along with all the most common diseases. So, this review emphasizes the disorders that affect the mare´s and foal´s health on peripartum period.